Secure E-mail system with cryptography using microsoft visual C# and pretty good privacy (PGP) [electronic resource] - 341582 Chee, Wing Fai (Skudai : Universiti Teknology Malaysia, 2004)
Project Paper (Sarjana Muda Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2004